The right to a healthy living environment in the context of the European Convention on Human Rights - Zagorc, Špela (Dignitas (Ljubljana), 2025)
Although more than 150 countries recognize the right to a healthy environment in their national constitutions, there is no autonomous, globally recognized human right to live in a healthy environment. Despite the absence of explicit rec-ognition of the human right to a healthy living environment in the international environment, it exists and is developing through the application of already existing internationally recognized human rights to environmental issues. the con-ducted analysis, presented in this Article, implicitly formu-lates the right to a healthy living environment as it stems from the EcHr and the case law of the EctHr. the presented Article is focused on the substantive and procedural aspects of essential EcHr rights that can be implicitly linked to the right to a healthy living environment, while also identifying and defining the most important factors that ensure the ef-fective enforcement and protection of the right to a healthy living environment in accordance with the EcHr. the pre-sented concept of a model of the right to a healthy living environment, as it implicitly derives from the EcHr and the EctHr, offers a broader insight into the right to a healthy living environment, together with extensive, yet fundamen-tal arguments stemming from the case law of the EctHr. Undoubtedly, the results of the conducted analysis contribute to raising awareness and strengthening environmental protection as well as protecting the rights of individuals in relation to the topic at the national level.
Keywords: case law; Človekove pravice; ECHR; ECtHR; EKČP; ESČP; healthy living environment; Mednarodna sodišča; pravica do zdravega življenjska okolja; protection of human rights; sodna praksa; varstvo človekovih pravic